A Tale of Hypertensive Retinopathy with Choroidopathy and Neuropathy in A Young Patient: A Sign of End Stage Renal Disease - Shruthy Vaishali Ramesh; Prasanna Venkatesh Ramesh; Ramesh Rajasekaran; Meena Kumari Ramesh; Prajnya Ray (Delhi Journal of Ophthalmology)
A 35 year old male patient presented with defective vision in the left eye associated with severe headache for past one week. On evaluation, the best corrected visual acuity of right eye (OD) was 20/20 and left eye (OS) was 20/40. Fundus evaluation revealed features suggestive of hypertensive retinopathy, choroidopathy and neuropathy. His blood pressure was 210/140 mm of Hg. Furthermore, on referral to Nephrologist, the patient was diagnosed with renal hypertension and was started on dialysis. Ophthalmic evaluation helped in diagnosing this life-threatening systemic condition; and the possibility of choroidal lesions, though less recognised have important implications in end organ damage.